Vibration and vibration-torsion levels of the S1 state of para-fluorotoluene in the 580–830 cm-1 range: interactions and coincidences - Tuttle, William D.; Gardner, Adrian M.; Whalley, Laura E.; Wright, Timothy G. (American Institute of Physics Publishing, 2017)
A study of the vibration and vibration-torsion levels of para-fluorotoluene (pFT) in the 580–830 cm-1 region is presented, where a number of features are located whose identity is complicated by interactions and overlap. We examine this region with a view to ascertaining the assignments of the bands; in particular, identifying those that arise from interactions involving various zero-order states (ZOSs) involving both vibrations and torsions. Resonance-enhanced multiphoton ionization (REMPI) is employed to identify the wavenumbers of the relevant transitions and subsequently zero-kinetic-energy (ZEKE) spectra are recorded to assign the various eigenstates. In some cases, a set of ZEKE spectra are recorded across the wavenumber range of a REMPI feature, and we construct what we term a two-dimensional ZEKE (2D-ZEKE) spectrum, which allows the changing ZOS contributions to the eigenstates to be ascertained. Assignment of the observed bands is aided by quantum chemical calculations and all b1 and a2 symmetry vibrational wavenumbers are now determined in the S1 state and cation, as well as those of the D10 vibration. We also compare with the activity seen in the corresponding S1 ←S0 spectrum of para-difluorobenzene.